2017
DOI: 10.3892/etm.2017.5645
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of chemokines and inflammatory cytokines for patient care following percutaneous nephrolithotripsy

Abstract: Abstract. Chemokines are a class of proteins with low molecular weight that serve important roles in the progression of inflammation. Percutaneous nephrolithotripsy is a surgical technique in which lasers or ultrasound are utilized to break down and/or remove kidney stones. In order to ensure a full recovery following surgery, effective patient care and nursing are required. In the present study, a total of 348 patients with kidney stones were recruited and the clinical importance of chemokines and inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…They suggest that IL-8 could be a marker as a screening test for urolithiasis. Wang et al [ 57 ] showed that the values of pro-inflammatory cytokines, including IL-8 in plasma, decreased in patients after percutaneous nephrolithotripsy and suggested that IL-8 can be used as a predictive tool for patients after this procedure.…”
Section: Urolithiasis Metabolic Acid Inflammation and Insulin Resistancementioning
confidence: 99%
“…They suggest that IL-8 could be a marker as a screening test for urolithiasis. Wang et al [ 57 ] showed that the values of pro-inflammatory cytokines, including IL-8 in plasma, decreased in patients after percutaneous nephrolithotripsy and suggested that IL-8 can be used as a predictive tool for patients after this procedure.…”
Section: Urolithiasis Metabolic Acid Inflammation and Insulin Resistancementioning
confidence: 99%